Métodos de síntesis en la hidrología urbana - Luna Caicedo, Nelson Oswaldo (1975)
The process of effective rainfall/direct runoff in simulated in two urban sub-basins, with extreme degrees of urbanization previously chosen, by means of the NASH techniques (equal reservoirs in a cascading sequence) and KRAIJENHOFF (decreasing parallel reservoirs). An optimization technique is presented (minimization of an Objetive Function), for each single basin, model, rainfall, and hydrograph, taking as an optimum solution a weighted value. The optimum values are correlated to Hydraulically Impervious rates which have been obtained by photointerpretation and the study of orthophotographs. Various comments are made as to maximum discharges expected throughout various return periods and in various states of land occupancy, convolutioning the instantaneous reactions of optimum model with typical rains.